Rasgos de personalidad y tipos de atención en estudiantes a choferes profesionales - Veloz Merizalde, Marcel Ginato (2020)
The main objective of this research was to determine the personality traits and types of attention in students who will become professional drivers, Riobamba 2019. The study sample was made up by 30 students from the “Sindicato de Choferes Profesionales de Riobamba”, or Union of Professional Drivers of Riobamba (in English). The methodology used was quantitative, bibliographic, with a non-experimental and cross-sectional design, it was on field and with a descriptive level. The technique implemented was the application of psychological tests, the instruments were the Salamanca questionnaire for the screening of personality traits, while for the variable of types of attention, the tests of direct and indirect digits were used, a subtest of the WAIS-III, Conners Continuous Performance Test (CPT-II) (CPT App) and the Trail Making Test (TMT App). Among the main results, it was evidenced that the traits considered psychopathological were Dependent with 16.67% and Anxious with 20%. Regarding the variable of types of attention, attentional coding in the direct order was normal with more prevalence, while in the reverse order there were many blunders in the sample, sustained attention and change of attention at appropriate levels and 63.33% have appropriate time ranges in focused attention. Based on the results obtained, a proposal of psychological strategies was developed with the aim of improving the levels of knowledge about personality traits and stimulating adequate attentional development, through psychological strategies for efficient personal growth and job performance in future professional drivers in the city of Riobamba.